ZVS based on dead-time analysis of three port half bridge converters - Phuong Vu; Manh Linh Nguyen; Viet Phuong Pham (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this research, the zero-voltage switching (ZVS) of the GaN FETs-based high frequency three-port half-bridge converter (TPHBC), which is capable of interfacing a renewable energy source, an energy storage and a load is discussed. To achieve ZVS, which plays a key role in power loss reduction of the high switching frequency converters, not only the parasitic elements but also the dead-time between two switches in one converter arm must be taken into account. This research gives a detail analysis about the influence of the dead-time on the ZVS condition. Based on the analysis, a minimum dead-time which guarantees not only the ZVS but also the safe operation of the converter is obtained. Simulations in various load condition of the TPHBC are carried out to verify the validity and effectiveness of the proposed method.